GAMMA RAY SPECTROMETRY OF ROCKS FROM A VOLCANIC SEQUENCE PENETRATED BY THE SG-1 BOREHOLE AND THE RADIOGENIC CONTRIBUTION TO THE TOTAL HEAT FLOW - Aliev Ch.S.; Zolotovitskaya T.A.; Ismailzade T.A. (My University, 2002)
Results derived from gamma-ray spectrometry studies of volcanic rocks in a depth interval of 3540-8150 m are presented. The rocks are shown to have low concentrations of radioactive elements, which is consistent with the clarke of basic igneous rocks close to calc-alkalic series of present island-arc systems. Potassium is present in all rocks of the volcanic sequence, whereas uranium and thorium are absent in some of its beds. Maximum U and Th concentrations are 410-4 % and 610-4 %, respectively. The Mesozoic sequence was subdivided into seven groups in accordance with associations of radioactive elements. The distribution of radioactive elements and their associations along the SG-1 section can be accepted as criteria for the differentiation of the volcanic sequence. Estimates of the radiogenic heat generation calculated for rocks of the volcanic sequence point to a considerable contribution of the radiogenic heat to the total heat flow. No proportionality exists between the radiogenic heat generation in the crust and measured heat flow. %, respectively. The Mesozoic sequence was subdivided into seven groups in accordance with associations of radioactive elements. The distribution of radioactive elements and their associations along the SG-1 section can be accepted as criteria for the differentiation of the volcanic sequence. Estimates of the radiogenic heat generation calculated for rocks of the volcanic sequence point to a considerable contribution of the radiogenic heat to the total heat flow. No proportionality exists between the radiogenic heat generation in the crust and measured heat flow.
Keywords: GAMMA RAY; SPECTROMETRY OF ROCKS; TOTAL HEAT FLOW; Mesozoic; Mesozoic; Мезозой